Vertical distraction osteogenesis of a reconstructed mandible with a free vascularized fibula flap: a report of two cases - Naoaki Saito; Akinori Funayama; Yoshiaki Arai; Daisuke Suda; Yoshiyuki Takata; Tadaharu Kobayashi (SpringerOpen, 2018)
Abstract Background The free vascularized fibula flap presents many advantages such as sufficient length of the bony segment, good vascularization, better quality of the bone, and a long vascular pedicle, but it is also associated with some disadvantages with regard to prosthetic rehabilitation because of its limited height. Improvement in bone height is necessary for ideal dental implant treatment of reconstructed mandibles. Case presentation For two squamous cell carcinoma patients, mandibular bone reconstruction was performed secondarily with the peroneal flap after tumor resection. Since the bone height was insufficient at the time of implant treatment, occlusion reconstruction by dental implant was performed after vertical distraction osteogenesis. Conclusions Vertical distraction osteogenesis is a suitable treatment option for alveolar ridge deficiency resulting from fibula transplantation for mandibular reconstruction following tumor surgery.